2016
DOI: 10.14442/jgfm.17.4_315
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Perforation due to Fish Bone Ingestion: a Case Report

Abstract: A 74-year-old man was admitted to our hospital due to low-grade fever and severe epigastric pain. Abdominal computed tomography revealed a linear structure surrounded by a small amount of air that had pierced the angular region of the gastric wall. Esophagogastroduodenoscopy showed that the structure was a fish bone. Gastric perforation due to fish bone ingestion is rare and almost all of the cases need surgical procedures. In this case, we endoscopically removed the foreign body with forceps and clipped the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…During the clinical course, since the fish bone migrated into the bile duct, there were no specific abnormalities, such as pain or inflammation associated with perforation. As such, we considered transpapillary foreign body migration as the most likely route of migration, as previously described [ 25 ]. In six cases (37.5%) reported in Japan, migration through the duodenal papilla was considered [ 10 , 15 – 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the clinical course, since the fish bone migrated into the bile duct, there were no specific abnormalities, such as pain or inflammation associated with perforation. As such, we considered transpapillary foreign body migration as the most likely route of migration, as previously described [ 25 ]. In six cases (37.5%) reported in Japan, migration through the duodenal papilla was considered [ 10 , 15 – 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unintentional ingestion of fish bones is common, and most fish bones pass through the gastrointestinal tract within a week, without symptoms or complications [1,2]. Gastrointestinal perforations occur in less than 1% of all patients, and may affect any segment from the esophagus to the rectum.…”
Section: Discussionmentioning
confidence: 99%
“…Fishbone penetration/perforation of the stomach is rare [3], the most common sites are the ileum, the ileocecal junction, and the rectosigmoid colon [4]. Accordingly, the diagnosis of fishbone penetration/perforation is clinically challenging, because a simple radiography imaging has a limited sensitivity of only 32%.…”
mentioning
confidence: 99%
“…Generally, surgery is the recommended treatment when there is a foreign body perforation [1]. Nevertheless, like Wada et al [3] and Ngan et al [5] described, if penetrating fishbones are identified early, namely in the absence of or with mild peritonitis, endoscopic extraction may be possible and should be attempted. There are several devices that can be used to retrieve this kind of sharp foreign bodies (rat-tooth, alligator-tooth, or shark-tooth), the choice of retrieval device is determined by the size and shape of the foreign body and by the endoscopist’s preference and practice [1, 2].…”
mentioning
confidence: 99%
See 1 more Smart Citation